2023
DOI: 10.1007/s12325-023-02604-z
|View full text |Cite
|
Sign up to set email alerts
|

People Diagnosed with Myasthenia Gravis have Lower health-related quality of life and Need More Medical and Caregiver Help in Comparison to the General Population: Analysis of Two Observational Studies

S. Dewilde,
G. Phillips,
S. Paci
et al.

Abstract: Introduction Myasthenia gravis (MG) is a neuromuscular disease causing extreme muscular fatigue, triggering problems with vision, swallowing, speech, mobility, dexterity, and breathing. This analysis intended to estimate the health-related quality-of-life impact, the medical burden, and the need for caregiver help of people diagnosed with MG. Methods MyRealWorld-MG (MRW) is an observational study among adults diagnosed with MG in 9 countries. The General Population Norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 70 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…The intention is to elevate the patient voice by providing objective, quantitative self-reported data that can be put into perspective by contrasting outcomes with a representative sample of the general population. This is a tandem paper to a similar study which identified lower utility values and higher need for medical care and caregiver help in patients with MG compared to the general population [9].…”
Section: Introductionmentioning
confidence: 71%
“…The intention is to elevate the patient voice by providing objective, quantitative self-reported data that can be put into perspective by contrasting outcomes with a representative sample of the general population. This is a tandem paper to a similar study which identified lower utility values and higher need for medical care and caregiver help in patients with MG compared to the general population [9].…”
Section: Introductionmentioning
confidence: 71%